A prática de indexação: análise da evolução de tendências teóricas e metodológicas - Silva, Maria Dos Remédios Da [UNESP]; Fujita, Mariângela Spotti Lopes [UNESP] (Pontifícia Universidade Católica de Campinas, 2004)
To contribute with a reflection on the indexer's practice, having in mind the evolution of the indexing process, the authors of this paper sought to assess the theoretical and methodological development of such process, through a survey of the literature, extracting from it the main trends and influences. The scrutiny of the relevant literature was systematized in two types of analyses: one, the analysis of fundamental literature in the area, and the other, that of experience stories. The first analysis was divided in three categories: theoretical and methodological definition, history, and aspects of indexing. These have allowed the authors to substantiate a constant concern on the part of the scholars, regarding the approach to the document as a subject and having in mind its recovery. The authors conclude that the emphasis in this process rests in the academic indexing-resultant of the outset of subject analysis carried out by the indexer. This second type of analysis is more directly influenced by the interfacing areas of Documentation Analysis - Linguistics, Logic and more recently, of sciences such as the Cognitive Psychology, which was approached in theoretical studies that did not prove deep enough yet. Once the logical, linguistic and cognitive aspects affecting document contents be better clarified, they will assist the indexing professionals in determining the topics actually involved in a document, and will allow them to accomplish a more effective conceptual analysis of such document.

Almejando contribuir com uma reflexão sobre a prática do indexador e tendo em vista a evolução do processo de indexação, os autores procuram identificar, pela revisão da literatura, o desenvolvimento teórico e metodológico de tal processo, extraindo as principais tendências e influências ali presentes. A revisão da literatura foi sistematizada por duas análises: a da literatura fundamental e a dos relatos de experiência. A primeira análise divide-se em três categorias: definição, história e aspectos teóricos e metodológicos da indexação, as quais permitiram evidenciar a constante preocupação, por parte dos estudiosos, com relação à abordagem do assunto do documento, tendo em vista sua recuperação. Com isso, conclui-se que a maior ênfase nesse processo está relacionada à indexação acadêmica _ resultante da concepção de análise de assunto assumida pelo indexador. Este segundo tipo de análise tem suas influências mais diretamente relacionadas às áreas de interface da Análise Documentária _ a Lingüística, a Lógica e a Psicologia Cognitiva, mais recentemente abordada pelos estudos teóricos, ainda não aprofundados. Quando estes aspectos lógicos, lingüísticos e cognitivos estiverem mais esclarecidos, permitirão ao indexador a realização de uma análise conceitual do documento mais efetiva, pois são estes aspectos que vão auxiliar na determinação da tematicidade do documento.
The indexing practice: a development analysis of theoretical and methodological trends
Keywords: indexação; história da indexação; metodologia de indexação; análise documentária; leitura documentária; indexation; history of the indexation; methodology of indexation; documentary analysis; documentary reading